Innovation markets, future Markets, or potential competition: How should competition authorities account for innovation competition in merger reviews? - Benjamin Kern (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
The relevant competitors in regard to innovation might, but not necessarily do, correspond to the identified competitors on actual product markets. Hence, the conventional analysis of product markets, in order to assess the potential anticompetitive effects of mergers, is insufficient to capture innovation competition in its full extent. As a consequence, the aim of this article is to introduce and compare the existing alternative approaches which can, in principle, be used for the assessment of anticompetitive innovation effects in merger review. By focusing on the applied U.S. Antitrust, it turns out that none of the existing approaches seems to be appropriate to fully account for innovation competition. However, the 'Innovation Market Analysis', the first framework especially designed for the assessment of innovation aspects, might still serve as a good starting point for the development of a revised assessment framework.
Keywords: B52; K21; L12; L41; O31; 330